PENGARUH KEMATIAN TERHADAP JUMLAH PENDUDUK DAN PERTUMBUHAN EKONOMI - Detia Adzra Athifah; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Mortality has a negative impact on demographics. The more the number of deaths increases, the lower the population will be. Population growth will increase, population growth is also very concerned about the death rate and birth rate in a region. This article reviews the effect of death on population and economic growth. This study aims to determine the effect of death on the population and to determine the impact of economic decline caused by death. The method used in this research is literature review, which is the process of analyzing and investigating relevant and published literature on a particular topic through various information (science journals, books, documents). In the study the author observed the effect of mortality on population and economic growth. The results of the study explain that population mortality has a significant negative impact on the population and economic growth of a country. For example, a high mortality rate in a productive age group can lead to a decrease in economic potential. The high mortality rate can also reflect the low quality of life of people in a country. In addition to the negative impact of high mortality rates, there is also a positive impact on economic growth, as higher population density can increase economic growth by increasing innovation and lowering transportation costs, although the effect is very small.